INVESTIGATION OF HYDROLYTIC ACTIVITY OF ENZYME PRODUCTS DURING HYDROLYSIS OF CELLULOSE IN COTTON FIBER - Soatov Askarali Mengdovulovich; Nazarov Kamolzhon Karimovich (Journals Park Publishing, 2022)
The cellulase complex of a number of bacterial and fungal enzymes is usually used for the enzymatic hydrolysis of cellulose-containing raw materials on an industrial scale. Currently, cellulase enzyme complexes are increasingly used in the textile, pulp and paper, food, feed, and other industries. In our studies, we studied the possibility of splitting cellulose (in the release of cotton fiber cellulose using three types of enzyme complexes.
Keywords: cellulose; celloviridin; pectofotedin